2013
DOI: 10.1155/2013/869506
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Picric Acid into Various Diluents

Abstract: Extraction constants, defined as ex = [HPic] o /[H + ][Pic − ], for picric acid (HPic) into ten diluents were spectrophotometrically determined at 298 K, where the subscript "o" refers to an organic (o) phase which is composed of the diluent. Their values for the HPic extraction into benzene and chloroform were fairly consistent with those reported before. From the ex values, distribution constants (D,HPic) of HPic into the o phases were estimated using the thermodynamic relation ex = D,HPic HPic , where HPic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Also, using the average log K HPic value (=0.55 ± 0.03) [8], we evaluated log K D,HPic to be 0.51 ± 0.03. This log K D,HPic value was the smallest of those (=0.89-1.97) [7] reported previously by the authors on the HPic extraction into various diluents.…”
Section: Plot Of Log K Exip Versus Log K DLcontrasting
confidence: 55%
See 3 more Smart Citations
“…Also, using the average log K HPic value (=0.55 ± 0.03) [8], we evaluated log K D,HPic to be 0.51 ± 0.03. This log K D,HPic value was the smallest of those (=0.89-1.97) [7] reported previously by the authors on the HPic extraction into various diluents.…”
Section: Plot Of Log K Exip Versus Log K DLcontrasting
confidence: 55%
“…Water amount of used 18C6 (>98.0%, Wako) was determined by the KarlFischer titration to be 0.062 ± 0.029% at N=4. The H(I) amount of an aqueous solution prepared from a commercial HPic (>99.5%, Wako) was determined by an acid-base titration [7]. Other reagents were the same as or similar to those employed previously [1,4].…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers added that extraction efficiency was positively affected from the existence of ammonium nitrate in the solution due to the salting out effect, while it decreased with the sulfates . At another study, Kudo et al evaluated ten different low-polar diluents and showed the positive effect of the functional groups in the structure of the organic diluent for the recovery. However, recovery efficiencies obtained with organic diluents in these studies were significantly low and need to be improved.…”
Section: Introductionmentioning
confidence: 99%